2016
DOI: 10.1177/2041731416656148
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent adult progenitor cells on an allograft scaffold facilitate the bone repair process

Abstract: Multipotent adult progenitor cells are a recently described population of stem cells derived from the bone marrow stroma. Research has demonstrated the potential of multipotent adult progenitor cells for treating ischemic injury and cardiovascular repair; however, understanding of multipotent adult progenitor cells in orthopedic applications remains limited. In this study, we evaluate the osteogenic and angiogenic capacity of multipotent adult progenitor cells, both in vitro and loaded onto demineralized bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 76 publications
(125 reference statements)
0
17
0
Order By: Relevance
“…While bone morphogenetic proteins have been recognized as stimulating osteogenesis and increasing osteoblastic activity, there is still a need for blood vessels to support the new bone tissue [ 22 ]. In vitro testing has demonstrated the ability of MAPC-based cells to secrete vascular endothelial growth factor (VEGF), CXCL-5, and interleukin-8, all of which are important in stimulating angiogenesis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While bone morphogenetic proteins have been recognized as stimulating osteogenesis and increasing osteoblastic activity, there is still a need for blood vessels to support the new bone tissue [ 22 ]. In vitro testing has demonstrated the ability of MAPC-based cells to secrete vascular endothelial growth factor (VEGF), CXCL-5, and interleukin-8, all of which are important in stimulating angiogenesis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting with exploring the effect of XFM media on MAPC cultures phenotype, MAPC thawed from liquid nitrogen seeded in a 2000 cells/cm 2 density and grown and maintained in XFM medium for 72 hours at 37°C were analyzed for morphology, proliferation, and viability. Phase-contrast micrographs showed that cells acquired their typical small, spindle-shaped, fibroblastic-like morphology [ 33 , 34 ]. This shape persisted over three days in culture as was previously shown [ 28 ] ( Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…MAPC have previously been shown to have promising therapeutic immunoregulatory effects driven ostensibly by their ability to produce paracrine effector molecules [ 35 ]. As such the secretory behavior of these cells has successfully shown to be influential in the treatment of a variety of clinical conditions, such as hind limb ischemia [ 36 ], multiple sclerosis [ 37 ], myelodysplastic syndrome [ 16 ], acute ischemic stroke [ 11 ], and bone repair [ 33 ]. However, unlike MSCs, MAPC have not yet been tested in vitro on corneal stromal cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Delivered MAPCs are expected to accelerate wound healing and to improve the quality of newly formed tissue via a multipronged approach. These cells can modulate the immune response to resolve inflammation; differentiate into skin progenitor cells, attract fibroblasts and keratinocytes, and stimulate ECM production for wound closure and dermal regeneration; secrete proangiogenic factors (e.g., CXCL5) and differentiate into endothelial cells for neovasculature formation; and recruit other endogenous stem cells that participate in wound healing . The paracrine effects of cytokines and growth factors secreted by MAPCs also suggest a way by which undelivered cells tethered on the functionalized patch can confer supplementary healing benefits, to augment those of delivered cells which often have short residence time in the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…They are nonimmunogenic, can be administered without tissue matching, survive in the hypoxic wound environment that typically inhibits healing, and possess broad differentiation potential into mesodermal, endodermal, and neuroectodermal cell types . MAPCs have been shown to improve tissue regeneration in a number of disease models such as myocardial infarction, ischemia, and brain, spinal cord, and bone injuries . Like MSCs, MAPCs secrete immunomodulatory, pro‐proliferative, and angiogenic factors important for wound healing.…”
Section: Introductionmentioning
confidence: 99%